2017
DOI: 10.1111/jnu.12276
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Sensitivity Among Clinical Nurses: A Descriptive Study

Abstract: Continuing education and formal courses on cultural sensitivity for nursing professionals are essential for optimal health outcomes. Thus, inequalities in health could be prevented and the quality of health care could be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 18 publications
4
43
1
15
Order By: Relevance
“…Compatible with this finding, many studies have revealed that nurses have high cultural sensitivity scores (Meydanlioglu, Arikan & Gozum, 2015). Yilmaz et al (2017) reported that the participants received 84.01 ± 9.1 for cultural sensitivity. The high cultural sensitivity scores in the present study can be explained by the fact that cultural sensitivity is dealt with in detail in the nursing curriculum of the school where the study was conducted.…”
Section: Discussionmentioning
confidence: 84%
“…Compatible with this finding, many studies have revealed that nurses have high cultural sensitivity scores (Meydanlioglu, Arikan & Gozum, 2015). Yilmaz et al (2017) reported that the participants received 84.01 ± 9.1 for cultural sensitivity. The high cultural sensitivity scores in the present study can be explained by the fact that cultural sensitivity is dealt with in detail in the nursing curriculum of the school where the study was conducted.…”
Section: Discussionmentioning
confidence: 84%
“…Conversely, in studies of Turkish nurses, different results regarding the association between cultural sensitivity and personal factors, such as learning expe- [9]. Another study investigating healthcare professional students' cultural sensitivity after being exposed to different cultures has reported significant changes of cultural sensitivities, which may be related to reflective activities, but not personal factors [10].…”
Section: Introductionmentioning
confidence: 97%
“…Göçler, doğal afetler, işsizlik, küreselleşmenin etkileri sonucunda insanların daha iyi bir yaşama sahip olma istekleri dünya üzerinde hızlı bir coğrafi hareketliliğin oluşmasına yol açmıştır (1). Bu hareketliliğin sonucunda bireyler gittikleri yerlere kendi kültürlerine ait özelliklerini götürmüşler (2) ve buralardaki insanlarla etkileşimde bulunarak çok kültürlü toplumları oluşturmuşlardır (2,3). Çeşitli nedenlerle toplumlarda oluşan bu değişim, farklı kültürel ve etnik kökene sahip bireylere kültürlerine uygun olarak hizmet etme gerekliliğini ortaya çıkarmıştır (4).…”
Section: Introductionunclassified